Pengembangan Taman Baca Sebagai Upaya Meningkatkan Literasi Anak Bangsa dalam Bingkai Moderasi Beragama - Mohammad Jauharul Arifin; Intan Brilyanti Sugiono; Arif Rahman Hakim (Abdimas Indonesian Journal, 2021)
Abstract. Mulyasari Village is an ex-transmigration village that has a diversity of religions including Islam and Hinduism that live side by side. Mulyasari village has a lot of potential, one of which is in the field of education, namely the existence of 3 educational institutions and 1 village library. There are serious problems in terms of people's reading interest where the literacy level and interest of the Mulyasari community is still relatively low. This paper specifically describes the efforts to make the public, especially children, aware of literacy through a reading garden that utilizes peace building as a strategy to strengthen religious moderation in Mulyasari Village. Through the Nusantara Collaborative Real Work Lecture program, for the development process of Mulyasari Village, we collaborated to build a sustainable community within the framework of religious moderation between Islam and Hinduism in Mulyasari Village using the CBPR method. CBPR (Community-Based Participatory Research) is a research model with stakeholders as the main key in the partnership approach process, where all relevant parties have responsibilities during the research process. The result of the Nusantara Collaboration KKN program is that there is a continuous community and through this reading park the interest and awareness of the Mulyasari Village community about the importance of literacy has increased significantly, this is indicated by the intensity of community and children's visits to the village reading park every week.